A mixed mechanochemical-ceramic solid-state synthesis as simple and cost effective route to high-performance LiNi0.5Mn1.5O4 spinels. (1st May 2017) - Agostini, M.; Matic, A.; Panero, S.; Croce, F.; Gunnella, R.; Reale, P.; Brutti, S.
Abstract: The implementation of high potential materials as positive electrodes in high energy Li-ion batteries requires to develop scalable and smart synthetic routes. In the case of the LiNi0.5 Mn1.5 O4 (LNMO) spinel material, a successful preparation strategy must drive the phase formation in order to obtain structural, morphological and surface properties capable to boost performances in lithium cells and minimize the electrolyte degradation. Here we discuss a novel simple and easily scalable mechanochemical synthetic route, followed by a high temperature annealing in air, to prepare LMNO materials starting from oxides. A synergic doping with chromium and iron has been incorporated, resulting in the spontaneous segregation of a CrOx -rich surface layer. The effect of the annealing temperature on the physico-chemical properties of the LMNO material has been investigated as well as the effect on the performances in Li-cells.